Diversity of endophytic and rhizosphere bacteria from pineapple (Ananas comosus) plant in semi-arid ecosystem - Rahayu Fitriani Wangsa Putrie; I Nyoman Pugeg Aryantha; IRIAWATI IRIAWATI; Sarjiya Antonius (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Putrie RFW, Aryantha INP, Iriawati, Antonius S. 2020. Diversity of endophytic and rhizosphere bacteria from pineapple (Ananas comosus) plant in semi-arid ecosystem. Biodiversitas 21: 3084-3093. The natural environment majorly influences plant microbiome diversity, in terms of endophytic and rhizobacteria. Pineapple (Ananas comosus L. Merr) has been identified as one of host plants with a capacity to grow in semiarid ecosystems. The intrinsic microbial symbiont composition is recognized in a specific ecological niche. The scientific information available is limited to the inoculants' ability to reduce plant stress, although the diversity in a semiarid ecosystem has not been studied. The aim of this research is to investigate the diversity of endophytic and rhizosphere bacteria obtained from pineapple in a semiarid ecosystem. A total of 117 culturable microbial isolates, dominated by Gram-positive bacteria were obtained from pineapple (88) and rhizosphere (29). The metagenomic analysis showed higher diversity and abundance in rhizospheres compared to the endophytes. Actinobacterium was identified as the most populated colony, while Proteobacterium was more prominent in the host plant. The Bacillus genera were recognized as the dominant symbiont genus. Therefore, the culturable isolates were further developed as candidate inoculants for microbe databases. This is expected to be useful in broadening theoretical knowledge.